Measuring the efficiency of public health services by DEA - Vitezić, Neda (Mednarodna revija za javno upravo, 2016)
Efficiency is one of the most important principles in public health services due to the strive for rationality and, at the same time, the need to strengthen quality. The aim of this research is to explore and analyse the suitability of DEA to measure the efficiency of a range of different services offered by institutes of public health in Croatia. DEA is a technique that is used to measure relative efficiency. It is traditionally used for non profit organizations. This technique has so far mostly been used in assessing solely the efficiency of hospitals and not other public health preventive services. For that reason the objective of this study is to identify units within one department of public health services that are relatively inefficient and to set targets for them based on the activities of units classified as efficient. We used data for 12 units (DMUs) for the period of two years, defining common inputs and outputs. The results obtained show projections of efficient and inefficient DMUs, projection of inefficient units at efficient frontier allows comparison between most similar units by efficiency and provides information on controllable inputs and outputs. This research has proven that relative efficiency obtained with DEA can be a useful tool in assessing efficiency of public health services on level of one institution and could support management decision-making process.
Keywords: DEA; efficiency; javno zdravstvo; merjenje uspešnosti; performance measurement; public health services; storitve; učinkovitost